Psychological Characteristics of Entrepreneurship Potentials among Vocational High School Students - Farradinna, Syarifah; Herawati, Icha; Mulyani, Ajeng Hari (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
This study investigates the psychological concept that affects the intention of vocational high school students to become entrepreneurs. This study aims to predict the most effective psychological step to demonstrate the psychological characteristics of entrepreneurs of vocational high school students. Participants in this study were vocational high school students in the Department of Mechanical and Building Engineering. 206 students were selected as the sample of the study with a random sampling technique. This study employed a set of questionnaires contains a measurement scale consisting of entrepreneurial capacity, entrepreneurial belief, entrepreneurial consciousness, entrepreneurial motivation, and entrepreneurial determination. Statistical analysis was performed with Confirmatory Factorial Analysis (CFA) to determine whether the fit model is unidimensional and to determine the significance value measurement model independently, assisted with statistical software Mplus. The results revealed that entrepreneurial belief and motivation are the highest factors. The results also reported that there is a significant difference in entrepreneurial belief in different gender. The entrepreneurial belief characteristics of male students were higher than female students. This implies that there is a need to emphasize psychological entrepreneurship education that leads to increased self-confidence in female students. In addition, it is necessary to do psycho-education to prepare students as entrepreneurs.